Socio-Cultural Factors Affecting Girls Retention in Primary Schools of Merikit Town Council Tororo District - Mebo Esther Angwalas (Uganda Christian University, 2024)
Girls’ retention in primary schools has remained a problem to school authorities and parents. Many girls are unable to enrol, remain in school and study to complete the education cycle. This study assessed socio-cultural factors affecting the retention of girls in primary schools in Meriktit Town Council of Tororo district. Specifically, the study was to find out how socio-cultural factors affect girls’ retention in primary schools visa vee other factors in Merikit Town Council, Tororo District. Other specific objectives included an examination of measures that can be adopted in order to improve on girls’ retention in primary schools of Merikit Town Council, Tororo District. The study used cross-sectional design to analyse data from the study area with the help of both qualitative and quantitative methods. The researcher collected data from 80 respondents in the study area who were selected using simple random and purpose sampling and questionnaires together with interview guide were used to collect data. The study found out that girls who are expected to take on the roles of women and mothers is a waste of time and money since they will get married and learn from there. Boys are considered as heirs thus are educated than girls and girls are expected to get married early for parents to get dowry. Study findings also showed that family poverty and unfriendly school environment makes girls lose interest in studying and hence making them drop out of school. Abuse of children’s rights forces girls to leave school and poor quality education discourages girls from attending school. The researcher therefore recommended that carrying out sensitization and advocacy campaigns in support of girl child education and reducing poverty through increasing household incomes so as to enable families get fees and sustain girls in school. Parents should be educated and sensitized on the values of the girl child education as well as eliminating negative cultural practices and norms that affect the general well-being of the girl child both in school and at home.